Now they can cope? The Green Deal and the contested meaning of sustainability in EU sectoral governance - Stockmann, Nils (Frontiers in Political Science, 2024)
The European Union (EU) has long discursively positioned itself as a global frontrunner for sustainability and climate protection. Nevertheless, substantive progress toward sustainability goals has not been reached in several governance areas, such as transport and mobility. Especially at the local scale, the highly complex and technocratic EU policy framework is confronted with increasingly polarized claim-making regarding ecological, social and economic problems. With its recent Green Deal governance architecture, the European Commission has sought to address this ideational and institutional fragmentation and resulting stalemate toward reaching “climate neutrality” by proposing ambitious sectoral policies and new governance instruments. This problem-driven paper exploratively investigates the ongoing reconfigurations the Green Deal induces within EU governance. Using the example of the urban mobility sector and employing an interpretive analysis of key policy documents and expert/stakeholder interviews, the paper links the literatures on EU governance architectures and norm dynamics. It discusses potentials and pitfalls for meaning-making processes in times of the socioecological polycrisis. Notably, it critically evaluates the Green Deal’s capacity to open and sustain spaces for translating sustainability across horizontally and vertically fragmented realms of EU governance.